INTEGRATION OF UKRAINIAN CHILDREN AND YOUTH USING DIGITAL TOOLS IN THE EDUCATIONAL ENVIRONMENT OF SLOVAKIA - Nelly Nychkalo; Nataliia Muranova; Olena Voliarska; Maria Matulcikova (Інформаційні технології і засоби навчання)
The article examines the issue of integration of Ukrainian children and youth into the educational environment of Slovakia. The purpose of the article is to highlight the results of the national assessment of the process of integration of Ukrainian school-age children using digital tools into the social and educational environment of Slovakia, identify problems and needs of subjects of the educational process, and provide relevant recommendations. General scientific and special research methods were used. We summarized the results of the general report of the study "Support for emigrants from Ukraine in education", which was conducted in Slovakia during 2022–2023 by the National Institute of Education and Youth in cooperation with the Ministry of Education, Science, Research and Sports of the Slovak Republic and in cooperation with the United Nations Children's Fund as well as the report "Distance education of students during the COVID-19 pandemic in the context of teacher training". It has been established that the integration of Ukrainian school-aged children into the educational environment of Slovakia also requires significant linguistic, educational and socio-psychological support from teachers and pedagogical workers. It was found that a wide range of digital tools and resources are used to organize the process of integration of Ukrainian children and students in Slovakia. It has been established that Slovak teachers use such digital tools as Microsoft Teams, Cisco Webex Meetings, Google Classroom, Zoom to integrate Ukrainian students into the educational environment. It has been proven that Slovakian society faces the problem of accelerating the integration of Ukrainian children, pupils and students by means of digital tools. The generalization of the results made it possible to draw up recommendations on the integration of Ukrainian school-age students by means of digital tools at the state, regional and educational institution levels that are recommended to be used in developing state policies and strategies in the field of teacher training both in Slovakia and in Ukraine. The article was funded by Next Generation EU through the Recovery and Resilience Plan for Slovakia under the project No. 09I03-03-V01-00058.